The plain man's pathways to heaven kinds of Christianity in post-Reformation England, 1570-1640 - Haigh, Christopher (Oxford University Press, 2007)
Offering a lively account of popular religion in England under Elizabeth I and the early Stuarts, a time when everyone had to go to church and almost everyone was religious to some extent, this book deals with the religious beliefs and practices of ordinary people - mainly by quoting their actual words.